Implementasi Kebijakan Dalam Menjaga Ketersediaan Pupuk Bersubsidi Bagi Petani Padi di Kecamatan Gunung Tuleh Kabupaten Pasaman Barat - Zulfikar, zulfahmi; Eriyanti, Fitri (Jurusan Ilmu Administrasi Negara, 2025)
This research aims to assess the effectiveness of the evaluation of the implementation of fertilizer subsidy policies for rice farmers in Gunung Tuleh District, West Pasaman Regency. The background of this research is the suboptimal distribution of subsidized fertilizers and the limited availability of fertilizers for farmers. This study was conducted using a qualitative approach, employing data collection techniques through interviews and document analysis. The results indicate that the implementation of the subsidized fertilizer distribution policy in Gunung Tuleh District, West Pasaman Regency, is proceeding well. It starts from the arrival of fertilizers from companies to the Regency/City, which are handed over to distributors and retailers who sell them to farmers' groups, and this process is done effectively. The implementation of the subsidized fertilizer distribution policy in Gunung Tuleh District, West Pasaman Regency, has been effective, as the distribution of subsidized fertilizers to farmers and farmers' groups meets their needs. Keywords: Implementation, Policy, Availability, Subsidized Fertilizer